Aesthetic value in classical antiquity - Sluiter, I.; Rosen, Ralph Mark. (Mnemosyne, Supplements, 2012)
How do people respond to and evaluate their sensory experiences of the natural and man-made world? What does it mean to speak of the 'value' of aesthetic phenomena? And in evaluating human arts and artifacts, what are the criteria for success or failure? The sixth in a series exploring 'ancient values', this book investigates from a variety of perspectives aesthetic value in classical antiquity. The essays explore not only the evaluative concepts and terms applied to the arts, but also the social and cultural ideologies of aesthetic value itself. Seventeen chapters range from the 'life without the Muses' to 'the Sublime', and from philosophical views to middle-brow and popular aesthetics. Aesthetic value in classical antiquity should be of interest to classicists, cultural and art historians, and philosophers.